Atores religiosos e construção da paz: a igreja católica no processo do acordo de paz na Colômbia (2012 -2016) - Félix, Kamila Alves (2021)
The 21st century has witnessed a growing importance of religion in the academic literature of International Relations, especially when playing relevant roles in the themes of peace and violence. At this conjuncture, Colombia emerges as a central actor, in which a myriad of actors finds themselves in conflicting disputes, but also seeking peace. Within this context, the current research presents the following issue: "How do religious actors, in particular the Catholic Church, influence the process of building peace in Colombia?" The hypothesis suggests that the Catholic Church, as part of an epistemic community of religious actors and historically active in the peace process, serves as an intermediary of local knowledge and behavior aimed at theological approaches capable of influencing the peacebuilding process in Colombia. The timeframe of the study covers the first negotiations until the signing of the Havana Agreement, that is, from October 2012 to September 2016. The research is divided into three chapters: chapter 1 presents the relationship between Religion, Peace Studies and Epistemic Community, in order to build a theoretical basis capable of providing guiding concepts for the following chapters; chapter 2 provides the historical context of the Colombian conflict, identifying the roots of the violence and the implications for the main points of the Havana Agreement; finally, chapter 3 centers the debate on explaining the role of religious actors involved in the peacebuilding process and presents the activities of Catholic religious actors as an epistemic community in the dynamics of peacebuilding in Colombia. The research results demonstrate that the activities of the Catholic Church are based on religious knowledge and expertise, added to its experience as a mediator of international conflicts, influencing the process of peacebuilding in Colombian society.